Prescribed medication for postoperative endodontic pain management by dentists in Taif, Saudi Arabia - Faisal K. Altalhi; Hassan T. Shawli; Ayman Mandorah; Bandar S. Shukr; Sami Dakhil Allah Alharthi; Ghada A. Althobiti; Saif K. Alzahrani (Saudi Journal of Oral Sciences)
Introduction: Endodontic treatment may require the prescription of analgesics. Current research is unclear regarding their use, especially after root canal therapy. Dentists over-prescribing them can negatively affect the patient’s health and well-being. Aims: This pilot study aimed to investigate the knowledge and patterns of postendodontic analgesic prescription among dentists in Saudi Arabia. Materials and Methods: Data were collected from 80 dentists practicing in the Taif region using a self-administered online survey. The survey consisted of three sections: demographics, analgesic prescription patterns, and prescription knowledge. The analysis was performed using descriptive statistics and linear regression models. Results and Discussion: About 96.3% of the dentists reported prescribing analgesics after endodontic treatment compared to 3.7% who do not. When pulpal conditions were considered, the most frequent condition for which dentists prescribed analgesics was symptomatic irreversible pulpitis (83.8%), followed by necrotic pulp (67.5%), and reversible pulpitis (65.0%). Regarding periapical pathology, the common conditions were symptomatic apical periodontitis (90.0%), followed by acute (76.3%) and chronic (63.7%) apical abscesses. The analgesics of choice for most dentists were “Ibrufen” which is a nonsteroidal anti-inflammatory drug. The majority had acceptable prescription knowledge, except in the “patient factors” domain. When the demographic factors were analyzed, lower knowledge level was seen among non-Saudi dentists (P = 0.001), and those who were working in public/governmental clinics (P = 0.059). Conclusions: The findings indicated that most dentists tended to overprescribe analgesics, with many of them having insufficient knowledge regarding the patient factors that need to be considered to select the most appropriate analgesic type. These findings highlight the importance of developing educational interventions, targeted mainly toward non-Saudi dentists, and those employed in public/governmental clinics.